2011
DOI: 10.1111/j.1365-2559.2011.03894.x
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization for human epidermal growth factor receptor 2 testing in gastric carcinoma: a comparison of fluorescence in-situ hybridization with a novel fully automated dual-colour silver in-situ hybridization method

Abstract: Aims:Amplification of the human epidermal growth factor receptor 2 (HER2) gene has been reported in gastric carcinoma (GC). Accordingly, trastuzumab plus chemotherapy has recently become the new standard treatment for HER2-positive advanced GCs. The aim was to compare the alleged gold standard for hybridization [fluorescence in-situ hybridization (FISH)] with a novel, fully automated brightfield dual-colour silver-enhanced in-situ hybridization (SISH) method.Methods and results:The studies series was comprised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 43 publications
2
24
1
1
Order By: Relevance
“…Eighteen patients (14%) were detected to have a positive HER2 status both in the biopsy and the resection material (concordance: 96.1%) (23). In our study, we found a higher rate of HER2 discordance in the primary GC and the paired metastasis compared with the rates reported in previous studies.…”
Section: Discussioncontrasting
confidence: 52%
“…Eighteen patients (14%) were detected to have a positive HER2 status both in the biopsy and the resection material (concordance: 96.1%) (23). In our study, we found a higher rate of HER2 discordance in the primary GC and the paired metastasis compared with the rates reported in previous studies.…”
Section: Discussioncontrasting
confidence: 52%
“…Our results are similar to the few studies published to date comparing these methods in gastric and GEJ tumors. [2][3][4] In accordance with our study, concordance rates of 96% and 100% were observed in 2 studies. 2,4 Langer et al 4 observed lower concordance, but this study was limited by the use of tissue microarrays including tissue cores from different tumor areas.…”
Section: Discussionsupporting
confidence: 95%
“…42,105 Many methods for detecting HER2 CNVs, including flourescence in situ hybridization, in situ hybridization, chromogenic in situ hybridization and silver in situ hybridization, have been demonstrated as effective approaches. 42,101,106 Moreover, the HER2:chr17 (chromosome 17) ratio may be an additional index to eliminate incorrect HER2 status determination in GC. 107 The utilization of molecularly targeted therapeutics against HER2 has emerged as a significant strategy for advanced GCs.…”
Section: Chromosomementioning
confidence: 99%